The multiple advantages of self-leadership in higher education: The role of health-promoting self-leadership among executive MBA students - Rune Bjerke (Administrative Sciences, 2024)
The purpose of this conceptual and explorative study is to document the advantages of health-promoting self-leadership practice. Professional certification programs are criticized due to a lack of practice among participants, involvement, and short duration. This study is based on self-leadership practices over several weeks of two executive MBA student classes from spring 2020 and 2021. A preliminary theoretical framework is developed suggesting that health-promoting self-leadership, which includes three orientations, has an impact on self-efficacy, mental fitness, and performance. Two different self-leadership classes with managers from the public and private sectors went through a self-development process as a semester project. The content analyses of 112 student reports unfolded students' self-development processes and results identified in diaries, notes, tables, training schedules, and reflections. The findings, based on two different samples and aggregated data, support the theoretical framework. Moreover, the processes of self-development and self-leadership seem to be advantageous for almost all managers. The health-promoting self-leadership practice improved managers' mental and physical fitness, energy balance, self-efficacy beliefs, and performance. These outcomes were achieved through physical activity, self-talk, meditative exercises, reward systems, visualizing, diet programs, and routines. The findings underscore the importance of self-development processes amongst managers, and that health-promoting self-leadership courses should last over several weeks.
Keywords: 350; health promoting self-leadership; mental fitness; performance; self-development process; self-efficacy- and energy-oriented self-leadership; value- and behavior-oriented self-leadership